Waspadai Dampak Penelantaran terhadap Perkembangan Sosial Emosional Anak - Nia Amanda (International Forum of Researchers and Lecturers, 2024)
Child neglect is a form of emotional violence that can have a significant impact on a child's social and emotional development. Neglect, which is characterized by a lack of attention, affection and support from parents or primary caregivers, often hinders children's ability to build interpersonal relationships, manage emotions and form self-confidence. This impact is not only short-term but also affects the child's life in adulthood, including the risk of mental disorders such as anxiety and depression. This article aims to analyze the impact of neglect on children's social and emotional development and provide recommendations for preventive and intervention steps to support children's optimal growth and development.